Models and Features of Student Exam Scheduling Services Using Website Information Technology - Argiyan Dwi Pritama; Rois Apriantoni; Virgiawan Virgiawan (Journal of Multimedia Trend and Technology, 2022)
One indicator of student progress in a tertiary institution is the implementation of seminar exams and one of the implementation techniques is seminar exams. In the current seminar exam scheduling system, the scheduling process still uses Microsoft Excel which makes sending and receiving data less real-time. The confirmation process carried out by the study program for the examining lecturers also seemed to be burdensome for the study program because the department was required to contact the selected lecturers one by one. Therefore, this study aims to create an information system for scheduling seminar exams which is expected to help academic administration and study programs in scheduling seminar exams. Data collection methods used are literature study, interviews and observation. While the system development method used is Prototyping. The results of this study are in the form of a university website prototype that is devoted to scheduling seminar exams by having a send confirmation feature to lecturers who will test via email.